Defining an appropriate threshold for apparent bias in international arbitration : a comparative study - Sigríður María Egilsdóttir 1993- (2019)
Arbitration, as a dispute resolution method, places particular emphasis on efficiency in the proceedings as well as party autonomy. But there is a third point of emphasis as well: the right to an independent and impartial tribunal. Indeed, respect for this bedrock legal principle is the rock upon which arbitration is built. Arbitral institutions and domestic courts have therefore created protections against actual and apparent bias in the arbitral panel. Yet, those protections vary substantially by jurisdictions, creating some uncertainty in the determination of the threshold for actionable bias. In turn, this creates challenges for states whose domestic law regarding arbitrator bias does not translate effectively to the field of international arbitration. This thesis describes the existing threshold for actionable apparent bias in several influential jurisdictions. The goal is two-fold. First, eliminating uncertainty regarding this important element of the arbitral proceedings will aid in jurisdiction selection, as well as in deciding whether or not to pursue a challenge against an arbitrator – an endeavor that might turn out both costly and time consuming. For this purpose, the author developed and applied a three-tier guideline, to categorize the severity threshold required by select states and arbitral institutions, for apparent bias to be considered actionable. Second, by understanding the reasons why different authorities adopted different standards, smaller nations like Iceland can draw important lessons in creating their own standards. The author recommends a standard for Iceland that is workable in Iceland’s legal and social context, and also makes sense in positioning Iceland as an attractive potential forum for international arbitration. Í gerðardómsrétti er veruleg áhersla lögð á skilvirni málsmeðferðar ásamt forræði aðila til að ákvarða hana. Ekki má þó gleyma þriðju áherslunni, þ.e. rétti aðila til að fá úrlausn hjá sjálfstæðum og óvilhöllum úrlausnaraðila. Þegar litið er til sögu ...